Markov paths, loops and fields ecole dâetâe de Probabilitâes de Saint-Flour XXXVIII-2008 - Le Jan, Y. (Yves) 1952- (Lecture notes in mathematics, 2011)
The purpose of these notes is to explore some simple relations between Markovian path and loop measures, the Poissonian ensembles of loops they determine, their occupation fields, uniform spanning trees, determinants, and Gaussian Markov fields such as the free field. These relations are first studied in complete generality for the finite discrete setting, then partly generalized to specific examples in infinite and continuous spaces